Disseminated Toxoplasma gondii Infection in an Adult Osprey (Pandion haliaetus) - Xiaobo Wang; Charles T. Talbot; Ji-Hang Yin; Anwar A. Kalalah; Chengming Wang; Joseph C. Newton (Veterinary Sciences, 2021)
An adult female osprey (Pandion haliaetus) was found weak and unable to fly in Auburn, Alabama in August 2019. The bird was captured and submitted to the Southeastern Raptor Center of the Auburn University College of Veterinary Medicine for evaluation. On presentation, the bird was thin with a body condition score of approximately 1.5 out of 5. The bird died during the examination and was submitted for necropsy. At the necropsy, there was a severe loss of muscle mass over the body, and the keel was prominent. The liver and spleen were moderately enlarged with pale tan to red foci randomly scattered throughout the parenchyma. A histopathologic observation revealed multifocal to coalescing areas of necrosis and hemorrhage with intralesional protozoans in the liver, spleen, lungs, kidney, sciatic nerve, esophagus, cerebrum, heart, and proventriculus. Immunohistochemistry using anti-Toxoplasma gondii-specific antibodies showed a strong positive labeling of the parasite. Semi-nested PCR, specific for the B1 gene of T. gondii, successfully identified T. gondii. This is the first confirmed case of T. gondii infection in an osprey.